Effect of gamma irradiation on survival of pahogenic bacteria Salmonella typhimurium , and Escherichia coli on chicken meat - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
The materials used were 96 chicken breast meat samples, weighing about 25 gram and sealed in polyethylene bags, respectively. All of samples were stored at 5 â 6Â°C over night prior to be used. Cultures were maintained and cloned on Triptych Soy Agar and propagated in 100 ml of triptych soy broth. The sterile meat was inoculated with enough cells of Salmonella and E. colt for a final population of -- 108 stationary phase cells/g. The samples were radiated by 6Â°Co sources in 7.6 kGy/hours dose rate at 0Â°C temperature, and after irradiation, they were stored at refrigerator temperature until being analyzed. All samples were divided into 2 groups namely 48 samples for S. typhimurium testing, and 48 samples for E. coli testing. Radiation doses were 0 (control), 1, 3, and 5 kGy. The effects of radiation were analyzed on 0, 4, 8, and 12 days of storage. The samples were assayed for colony forming unit/g by standard spread plate procedures using salmonellashigella agar to Salmonella, Mac Conkay Agar for E. colt and plate count agar for total microbial with serial dilutions in sterile peptone water 9.1%. The data were analyzed by using analysis of variance from split plot design (4 X 4) with 3 replications. Duncan's multiple range test was used to determine the mean differences. The results showed that the effects of radiation doses were highly significant (P... Keywords: Salmonella Typhimurim, Escherichia coli, Gamma Irradiation, Chicken Meat